Kinetically stabilized 1,3-diarylisobenzofurans and the possibility of preparing large, persistent isoacenofurans with unusually small HOMO–LUMO gaps - Liu, Qian; Miller, Glen P. (Beilstein Journal of Organic Chemistry, 2024)
DFT calculations demonstrate that an isoacenofuran of any size possesses a smaller HOMO–LUMO gap than the corresponding acene bearing an isoelectronic π-system (i.e., the same total number of rings). Isoacenofurans show limited stability due in part to the highly reactive 1,3-carbons of the furan ring. Both 1,3-dimesitylisobenzofuran and 1,3-di(2’,4’,6’-triethylphenyl)isobenzofuran, each bearing sterically congesting ortho-alkyl groups on their phenyl substituents, have been synthesized and shown to adopt non-planar conformations with the ortho-alkyl groups located above and below the most reactive 1,3-carbons of the furan ring. These bulky substituents provide a strong measure of kinetic stabilization. Thus, 1,3-dimesitylisobenzofuran and 1,3-di(2’,4’,6’-triethylphenyl)isobenzofuran are significantly less reactive than 1,3-diphenylisobenzofuran toward the strong dienophiles DMAD and acrylonitrile. The insights gained here suggest that the synthesis of large, persistent, kinetically stabilized isoacenofurans with unusually small HOMO–LUMO gaps is achievable. As such, these molecules deserve increased attention as potential p-type organic semiconductors.
Keywords: acene; DFT calculation; highly delocalized π-system; isoacenofuran; isobenzofuran; kinetically stabilized; organic semiconductor; small HOMO–LUMO gap; synthesis